PENINGKATAN MUTU BIJI KAKAO MENGGUNAKAN TEKNOLOGI FERMENTASI DI DESA MASARI, PARIGI MOUTONG - Priyantono, Eko; Fariroh, Indri (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Masari village is one of the cocoa production centers in Parigi Moutong regency, but in recent years cocoa production has decreased. The decline in cocoa production was due to the low selling value of cocoa beans, thereby reducing farmers' income. Farmers uncertain income caused the transition of crop commodities into plantation and food crops. The low selling value of cocoa beans was caused by the low quality of cocoa beans. One of the factors that caused the low quality of beans was post-harvest management, which is the cocoa bean fermentation process that is rarely done by the farmers. This community service program aims to provide knowledge about the correct bean fermentation method so they can improve the quality of cocoa beans. Service activities are carried out using counseling and training methods followed by demonstrations on how to ferment cocoa beans. In general, the counseling activity about the selection of cocoa pods that are ready to be harvested and fermentation procedures went well. The seed demonstration activity was also successful which was indicated by brown cocoa beans and had a fragrant smell. The target community already can carry out a good cocoa bean fermentation process. Cocoa bean fermentation technology can be used to improve the physical and chemical quality of cocoa beans so it can increase the value and sales of cocoa beans. The increase in sales will encourage farmers to develop a cocoa-based farming system.